The war correspondent - McLaughlin, Greg (Knowledge Unlatched - Round 2., 2016)
The War Correspondent looks at the role of the war reporter today: the attractions and the risks of the job; the challenge of objectivity and impartiality in the war zone; the danger of journalistic independence being compromised by military control, censorship, and public relations; as well as the commercial and technological pressures of an intensely concentrated, competitive news media environment. This new edition substantially updates the original, ending with an extended section on the return of history and ideology to the reporting of international conflict, and interviews with prominent war and foreign correspondents including John Pilger, Robert Fisk, Mary Dvesky, and Alex Thomson.